2020
DOI: 10.1016/j.ejor.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Can deep learning predict risky retail investors? A case study in financial risk behavior forecasting

Abstract: The paper examines the potential of deep learning to support decisions in financial risk management.We develop a deep learning model for predicting whether individual spread traders secure profits from future trades. This task embodies typical modeling challenges faced in risk and behavior forecasting.Conventional machine learning requires data that is representative of the feature-target relationship and relies on the often costly development, maintenance, and revision of handcrafted features. Consequently, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 56 publications
1
23
0
1
Order By: Relevance
“…Las técnicas de machine learning demuestran resultados positivos en análisis de riesgos financieros; específicamente, el aprendizaje profundo (Deep learning); la implementación de redes neuronales con un número alto de capas ocultas, permiten solucionar inconvenientes que presentan las técnicas más comunes del aprendizaje de máquina, facilitando evadir los tediosos pasos de la ingeniería de características (feature engineering), pues el deeplearning demuestra su capacidad para abstraer características informativas de manera autónoma; además los resultados de predicción de los modelos de redes neuronales profundas (DNN) resultan tener más exactitud respecto a los clasificadores habituales, concluyendo que las DNN son una herramienta útil para apoyar la toma de decisiones en el caso de estudio de riesgos financieros (Kim y Yang, 2019).…”
Section: Discusión De Resultadosunclassified
“…Las técnicas de machine learning demuestran resultados positivos en análisis de riesgos financieros; específicamente, el aprendizaje profundo (Deep learning); la implementación de redes neuronales con un número alto de capas ocultas, permiten solucionar inconvenientes que presentan las técnicas más comunes del aprendizaje de máquina, facilitando evadir los tediosos pasos de la ingeniería de características (feature engineering), pues el deeplearning demuestra su capacidad para abstraer características informativas de manera autónoma; además los resultados de predicción de los modelos de redes neuronales profundas (DNN) resultan tener más exactitud respecto a los clasificadores habituales, concluyendo que las DNN son una herramienta útil para apoyar la toma de decisiones en el caso de estudio de riesgos financieros (Kim y Yang, 2019).…”
Section: Discusión De Resultadosunclassified
“…When evaluated with an application to customer retention in a Canadian retail financial institution, the deep ensemble classifier produced outstanding performance, even with largely unbalanced customer data. The superiority of deep learning methods over traditional classification methods for predicting bank customer churn was shown in [40]. The results from the experiments showed that time-sequenced data used in a recurrent neural network-based long short-term memory (LSTM) model outperformed the baseline models when precision and recall were used as the metrics.…”
Section: Deep Learning Methods For Churn Management In the Banking Sectormentioning
confidence: 99%
“…The application of machine learning is nothing new in the case of bankruptcy models. For bankruptcy prediction, Zhou and Lai [60] effectively used the AdaBoost algorithm combined with imputation, while Kim et al [61] examined the benefits of deep learning on decision-making in financial risk management. Liu and Liu [18] used LSTM models combined with block-chain technology to increase financial performance and reduce risks.…”
Section: Literature Reviewmentioning
confidence: 99%